Utilization of cassava flour along with the addition of gluten for the preparation of noodles - Sangroula, Adit; Rai, Kishor; Acharya, Priti; Ghimire, Nepoliyan; Sherma, Girija; Giri, Saru; Khadka, Sabina; Ghimire, Himalaya; Dahal, Ramila (International Journal on Food, Agriculture and Natural Resources, 2024)
The aim of the study was to utilize the cassava flour in the preparation of noodles. Wheat flour, cassava flour and gluten were mixed in calculated amounts to produce noodles in the ratio (cassava flour:wheat flour:gluten) of 0:100:0, 92.5:0:7.5, 23.125:65.625:11.25, 42.5:42.5:15, 23.125:73.125:3.75, 65.625:23.125:11.25, 50:50:0, 0:92.5:7.5, 0:85:15, 85:0:15 and named as sample A, B, C, D, E, F, G, H, I and J respectively. The yield of cassava flour was found to be 43.1%. Sensory comparison elected the sample C containing 65.625% wheat flour, 23.125% cassava flour and 11.25% gluten as the best. The moisture content, protein, fat, ash, crude fiber and carbohydrate and cooking time of sample C was found to be 9.37±0.31%, 18.70±0.14%, 1.20±0.04%, 1.26±0.01%, 1.80±0.03%, 77.04±0.29% and 6±0.3 min respectively. When compared with wheat flour noodle, crude fiber and protein was found to be greater. Higher water absorption and volumetric expansion with low cooking loss was found in cassava flour used noodle. Statistical analysis (ANOVA at 5% level of significance (p<0.005) shows significant difference in all attributes. The cyanide content of the cassava flour was found to be 5.63±0.20 mg/kg which is within safe level i.e. 10 mg Hydrogen cyanide /kg dry wt. set the by Food and Agriculture Organization /World Health Organization.